Diversity of Butterflies (Lepidoptera: Rhopalocera) in Sumber Clangap and Waduk Selorejo, East Java - Fariska Nur Ashari; Nur Rizatul Addiniyah; Hayyin Nurul Aini (Biota, 2019)
Diversity of butterflies in various habitats very diverse, and it is one of them in the region Sumber Clangapand Waduk Selorejo. It has seen from the combination of colors and which wing shape varies. In this, bothregions were chosen because it had been affected by Mount Kelud eruption, which causes damage to thesurrounding area. The purpose of this research is to know the diversity of butterflies (Lepidoptera:Rhopalocera) in the region of Sumber Clangap and Waduk Selorejo, East Java. This research wasconducted on 26-29 January 2019. Sampling has taken by the method of Belt transect along the transectpath randomly with a technique snapshot experiment and a sweeping technique. Based on theobservations obtained 3 of the same family, Nymphalidae, Pieridae, and Papillionidae. The butterflydiversity in Waduk Selorejo belongs to low, whereas in Sumber Clangap are classified by index Shannon-Winner = 0.38 H ' and H ' = 2.47. Found eight types of butterflies from 3 families with a total of 13 speciesand has a value of H ' =2.47.